A study of the relationship between the poetry and criticism of Ezra Pound 1908-1920 - De Villiers, André Rex Wepener (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1959)
From the preface: The purpose of this thesis is exposition rather than criticism. Pound's position in the hierarchy of the 'New Criticism' would provide an extremely interesting subject; but I have rather tried to outline; the standards which he has laid down as being central in the technics of good poetry and to show how closely he has adhered to them in his own verse. I have limited the period to be discussed because all of the essential principles which he employs in his writing after 1920 are discernible in the body of his work published before that date.
Keywords: Pound, Ezra, 1885-1972 -- Criticism and interpretation